Deep eutectic solvent-assisted carbon quantum dots from biomass Triticum aestivum: A fluorescent sensor for nanomolar detection of dual analytes mercury (Ⅱ) and glutathione - Shivam Khare; Neeraj Sohal; Mandeep Kaur; Banibrata Maity (Heliyon)
Deep eutectic solvents (DESs) have attracted significant attention in recent years due to its environment friendly characteristics and its participation in the multi-heteroatom doping of carbon quantum dots (CQDs). In this work, we present a simple, fast, and environment-friendly microwave synthesis approach for the synthesis of DES-assisted nitrogen and chloride co-doped CQDs (N,Cl-CQDs) using a choline chloride-urea based DES. A biomass-based precursor, i.e., wheatgrass (Triticum aestivum), has been used as a carbon source. Transmission electron microscopy (TEM) showed the spherical shape with average 1.75 nm particle diameter of prepared CQDs. The surface functionality and chemical composition of prepared N,Cl-CQDs were determined by X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectroscopic techniques. The N,Cl-CQDs obtained a high quantum yield (QY), i.e., 36 %, compared to undoped CQDs, which were synthesized in an aqueous medium (QY = 15 %). The prepared N,Cl-CQDs showed significant properties such as excellent photostability, favorable water solubility, and high optical stability. N,Cl-CQDs were used as sensing platform for the detection of Hg2+ ions and GSH with LOD value of 39 nM and 43 nM, respectively. The fluorescence quenching mechanism was confirmed by several photophysical parameters, such as average lifetime values, radiative rate constant (kr), non-radiative rate constant (knr) and others. Furthermore, the current sensing system's viability is also tested in a river water sample for the detection of Hg2+. The N,Cl-CQDs prepared in this study exhibited a reduced detection limit and a broad linear range by an easy, environmentally friendly, and rapid method for detecting GSH and Hg2+ ions.